Reflections on Certain Witnesses Protective Measures Under the Rome Statute of the International Criminal Court - Romina Beqiri (European Scientific Journal, ESJ, 2017)
The witness protection framework at the International Criminal Court (ICC) was made to comply with internationally recognized standards of fundamental human rights, with international standards of fair trial and due process. Its purpose is not only to ensure protection of the physical and psychological integrity of witnesses testifying before the Court but also to ensure respect for the individual rights of the accused and the legitimacy of the proceedings to establish the truth and punish the perpetrators. This article focuses on the ICC’s liberal approach in procedural matters by enriching the jurisprudence and the case-law with principles of application and granting of protective measures. Hence, this article aims at analyzing the legal provisions governing some certain witness protective measures under the ICC legal framework as well as reflections of recent ICC case-law; the practicalities of granting protective measures to witnesses versus concerns in the implementation.